Respuestas

2013-07-23T02:32:23+02:00


TEOREMASSSSSSSSSSSSSS:::::
(a + b )2      = a2 + 2ab + b2

( x  +  6 )2   =   X^   +  2X(6)  +  6^
                  =   X^   +  12X     + 36

(a - b )2       = a2 - 2ab + b2
(  X -   7)2    = X^     -    2X(7) +  7^
                  =  X^    -    14X    + 49


(   x+   9)3   = X3     +  9al cubo  +  3x9 ( x + 9 )
                   = X3     + 279  + 27X (X + 9)


 (x  -   12)3  = X3     -  (12)al cubo  -  3x12( x - 12)
                  = X3    - 1728  -36x( x - 12)